KAPASITAS DAN SUDUT PISAU EFEKTIF PADA MESIN PENGIRIS BAWANG BERPISAU VERTIKAL DENGAN PUTARAN ROTOR 2OO RPM - -, Sutomo (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2004)
Onion's frying increase more delicious of fried rice, fried noodle etc. Sometimes onion's farmers have some problem, one of their problem is low price onion's product. Better they sliced their onions and fry it in order to have more economic of their product. lf the slicing process use engine, so this engine will help them to increase the slicing onion's product. Base on cutter rotor rotation is 200 rpm, research would like to know the effective of capacity and cutter angle with variables diameter is small up to big. The result of this research are : the capacity of small onions'diameter is (0.063 + 0.0016). 102 kg/sec. For middle diameter (r < o< 2.5 cm)is (0.04g t o.ooi+). 10 kg/sec. For big diameter (O> 2.5 cm) is (0.032 + 0.0019). t0-2 kg/sec. Ail of thesecapacity based on rotor's speed is 200 rpm and the cutter angle is 4o and slicing onion is a good thickness for fried onions.